Retrotransposon‐derived p53 binding sites enhance telomere maintenance and genome protection. (19th August 2016) - Lieberman, Paul M.
Abstract : Tumor suppressor protein 53 (p53) plays a central role in the control of genome stability, acting primarily through the transcriptional activation of stress‐response genes. However, many p53 binding sites are located at genomic locations with no obvious regulatory‐link to known stress‐response genes. We recently discovered p53 binding sites within retrotransposon‐derived elements in human and mouse subtelomeres. These retrotransposon‐derived p53 binding sites protected chromosome ends through transcription activation of telomere repeat RNA, as well as through the direct modification of local chromatin structure in response to DNA damage. Based on these findings, I hypothesize that a class of p53 binding sites, including the retrotransposon‐derived p53‐sites found in subtlomeres, provide a primary function in genome stability by mounting a direct and local protective chromatin‐response to DNA damage. I speculate that retrotransposon‐derived p53 binding sites share features with telomere‐repeats through an evolutionary drive to monitor and maintain genome integrity. Abstract : The p53 binding sites in human subtelomeres retain features of retrotransposons. We hypothesize that retrotransposon‐derived p53 binding sites function to modify local chromatin in response to genotoxic stress and enhance DNA repair activities at sites of genome fragility, such as telomere repeats.